Prevalence of computer vision syndrome in Erbil - Ahmed, Dler Jalal; Alwan, Eman Hussein (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and objective: Nearly all colleges, universities and homes today are regularly using video display terminals, such as computer, iPad, mobile, and TV. Very little research has been carried out on Kurdish users to reveal the effect of video display terminals on the eye and vision. This study aimed to evaluate the prevalence of computer vision syndrome among computer users. Methods: A hospital based cross-sectional study was conducted in the Ophthalmology Department of Rizgary and Erbil teaching hospitals in Erbil city. Those used computers in the months preceding the date of this study were included in the study. Results: Among 173 participants aged between 8 to 48 years (mean age of 23.28±6.6 years), the prevalence of computer vision syndrome found to be 89.65%. The most disturbing symptom was eye irritation (79.8%), followed by blurred vision(75.7%). Participants who were using visual display terminals for more than six hours per day were at higher risk of developing nearly all symptoms of computer vision syndrome. Significant correlation was found between time-consuming on computer and symptoms such as headache (P <0.001), redness (P <0.001), eye irritation (P <0.001), blurred vision (P <0.001) and neck pain (P <0.001). Conclusion: The present study demonstrates that more than three-fourths of the participants had one of the symptoms of computer vision syndrome while working on visual display terminals.